Autoimmune central diabetes insipidus in a patient with ureaplasma urealyticum infection and review on new triggers of immune response - Giuseppe Murdaca; Rodolfo Russo; Francesca Spanò; Diego Ferone; Manuela Albertelli; Angelo Schenone; Miriam Contatore; Andrea Guastalla; Annamaria De Bellis; Giacomo Garibotto; Francesco Puppo (Archives of Endocrinology and Metabolism, 2015)
Diabetes insipidus is a disease in which large volumes of dilute urine (polyuria) are excreted due to vasopressin (AVP) deficiency [central diabetes insipidus (CDI)] or to AVP resistance (nephrogenic diabetes insipidus). In the majority of patients, the occurrence of CDI is related to the destruction or degeneration of neurons of the hypothalamic supraoptic and paraventricular nuclei. The most common and well recognized causes include local inflammatory or autoimmune diseases, vascular disorders, Langerhans cell histiocytosis (LCH), sarcoidosis, tumors such as germinoma/craniopharyngioma or metastases, traumatic brain injuries, intracranial surgery, and midline cerebral and cranial malformations. Here we have the opportunity to describe an unusual case of female patient who developed autoimmune CDI following ureaplasma urealyticum infection and to review the literature on this uncommon feature. Moreover, we also discussed the potential mechanisms by which ureaplasma urealyticum might favor the development of autoimmune CDI.